Promoting healthy eating: The intervening role of health and nutrition-related claims in food advertisements. (December 2022) - Pan, Po-Lin; Bhandari, Manu; Meng, Juan
Objective: Factors contributing to the obesity epidemic have powerful effects on people who are frequently exposed to the extensive advertisement of unhealthy foods. This study aimed to examine how consumers' attitudes towards health and nutrition-related (HNR) claims in food advertisements affected their healthy food choice (HFC) and how online searching for nutrition information (OSNI) about food products mediated the impact of obesity knowledge on HFC. Method: An online survey was conducted using Amazon Mechanical Turk. A total of 897 participants were recruited, with 484 women and 380 men. A moderated mediation analysis using PROCESS was conducted. Results: OSNI was found to mediate the impact of obesity knowledge on HFC. The extent to which consumers' obesity knowledge influenced their HFC depended on consumers' attitudes towards HNR claims in food advertisements. The direct effect of consumers' obesity knowledge on their HFC was moderated by their attitudes towards HNR claims in food advertisements. Conclusion: Both theoretical and practical insights into the dynamic effects on HFC were identified in response to the use of HNR claims in food advertisements as a persuasive strategy for promoting healthy eating. Healthcare professionals and health educators working to address obesity issues should craft more useful online health and nutrition information for consumers who are considering eating healthier foods. In addition, more helpful HNR claims in food advertisements should be developed so as to promote healthy food products, especially for consumers with limited obesity knowledge.